Wallander. Season 1 [videorecording (DVD)] - Mankell, Henning, 1948-2015; Branagh, Kenneth; Warner, David, 1941-; Spark, Jeany, 1982-; Mankell, Henning, 1948-2015; Mankell, Henning, 1948-2015; Mankell, Henning, 1948-2015 (BBC Video : 2 Entertain ; distributed in the USA and Canada by Warner Home Video, 2009)
Three crime dramas based on the best selling novels by Henning Mankell. They follow Inspector Kurt Wallander, a disillusioned everyman, as he struggles against a rising tide of violence in southern Sweden.